Prevalence of Stress among Physiotherapy Students during Clinical Placement in Lahore, Pakistan - Nouman, Sehar; Zia, Kiran; Asadullah, Mariya; Khalid, Raheema; Khalid, Aqsa (Indus Journal of Bioscience Research, 2025)
Background: Psychologically stress is defined as a negative discern of psychic breakdown and oppression. Occupational stress is the stress that absorb by individual during his work task like uncomfortable environment for work, overload, cannot meet the expenditure etc. Objective: To determine the prevalence of stress among physiotherapy students during clinical placements. Material and Methods: A cross-sectional study was conducted at UHS Lahore, and cluster sampling technique was used to collect data. Sample size of the study was 92. In sample, students of DPT 4th and 5th year from universities of health and sciences took part in this study according to the limitations of the study. Close ended questionnaire (workplace stress scale) used to collect data and questionnaire was generated in google forms due to COVID-19 situation. Result: Among all the students 6(6.52%) students feel no stress, 34(36.96%) feel low, 34(36.96%) feel moderate, 17(18.48%) feel severe and 1(1.09%) feel very severe stress. In these students, 81 females and 11 males with the equal number of participants from 4th and 5th year DPT students. Conclusion: Stress is a negative feeling which is an emotional strain. The stress is high when the workload is high, and the person is unable to cope up stress. It is harmful both for that person and the placement because it effects on their output and self-efficacy. As per conclusion and recommendations to cope up with the stress of those students we need to take several steps which will be helpful for the students as well as for the future researchers.